Cold War in the Islamic World : Saudi Arabia, Iran and the Struggle for Supremacy - Hiro, Dilip (India HarperCollins Publishers, 2018)
The foundational schism between Sunni Arabia and Shia Persia manifests itself in geopolitics, as Kingdom and Islamic Republic compete.
Include Index
Keywords: Saudi Arabia -- Foreign relations -- Iran -- Iran -- Foreign relations -- Saudi Arabia